Physical and Digital Security in Schools and Educational Institutions Preliminary Study: Security Organisation in Schools and Educational Institutions - Ryszard SZYNOWSKI (Communications of International Proceedings, 2020)
The proposed study topic is of significant cognitive and application importance. In recent years, the issue of ensuring security in the school environment has been the focus of attention of educational authorities, parents and students, as well as scholars, which is why the researchers of the WSB University in Dąbrowa Górnicza joined forces with the Department of Education of the Municipal Office in Jaworzno to jointly undertake the “Physical and digital security in schools and educational institutions” project, the main objective of which will be the development of solutions ensuring physical and digital security of children and youth in schools and educational institutions in Jaworzno. This paper outlines the preliminary results of the first stage of the survey conducted in the environment of school headmasters and headmistresses, as well as managers of educational institutions. The objective of this preliminary study was the diagnosis of the scale and types of threats concerning physical security of children and youth, as well as the analysis of the process of organising security in schools and educational institutions by heads and managers of these institutions.
Keywords: Schools and educational institutions; physical security; digital security; external threats; internal threats; digital threats; security organisation.